Wilayatul Hisbah’s (WH) strategy to enforce the law against Khalwat case in Ujung Karang West Aceh Regency - Arfriani Maifizar (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2022)
This study seeks to understand Wilayatul Hisbah’s strategy in minimizing violations of Islamic sharia in relation to the khalwat case in the community, especially in Ujung Karang, West Aceh Regency. Ujung Karang is a coastal area visited by many local tourists and is also open to national and international tourism. Yet, there have been some teenagers, youths and young women who have traveled to these tourism regions and violated Islamic law by conducting khalwat such as at dimly lit cafes. The purpose of this study is to explore strategies, roles, functions, and obstacles faced by Wilayatul Hisbah when carrying out their duties in Ujung Karang. The research method used is a qualitative method with a constructivist paradigm. Data collection technique involves mainly in-depth interviews with key informants from Wilayatul Hisbah’s personnel, community leaders, and religious leaders. In addition, it also obtains secondary data regarding the violations of the Islamic law, namely khalwat. The results of this study illustrate that Wilayatul Hisbah's strategy in preventing khalwat in Ujung Karang includes socialization of qanun (principles) through spreading brochures and banners, conducting routine patrols and curfew, as well as coaching and building cooperation with the local community.